A Study On S.R.P. And S.P.M. Dropouts In Penang. - Navaratnam, V.; Sulaiman, Aminudin; Tan, Bee Leng (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1991)
This report presents findings from an analysis of data collected on school dropouts from four examination groups: S.R.P. 1985, S.P.M. 1987. S.R.P. 1987 -and S.P.M. 1989. The purpose of this study i~ to examine the activities of the dropouts such as deviancy, criminality, employment or unemployment and courses pursued. The areas which were examined include socio-demographic background, educational background, drug use history, >deviancy, criminality and activities after dropping out of school.